High-resolution body wave tomography beneath the SVEKALAPKO array: I. A priori three-dimensional crustal model and associated traveltime effects on teleseismic wave fronts - Sandoval, Senén; Kissling, Edi; Ansorge, Jörg (2017)
Assessment of contributions from shallow lithosphere to teleseismic wave front distortion is a prerequisite for high-resolution regional teleseismic tomography. Several methods have been proposed in the past for the correction of these effects, e.g. application of station correction terms. We propose an approach that is independent of the subsequent inversion and uses the available a priori knowledge of the crustal structure to calculate crustal traveltime effects of teleseismic wave fronts. Our approach involves the construction of a 3-D crustal model based on controlled source seismology data and calculation of the associated traveltime anomalies for incoming teleseismic wave fronts. The model for central Fennoscandia shows a maximum crustal thickness of 64 km and includes a high-velocity lower crust as derived for parts of the study area by previous authors. Traveltimes calculated using finite differences for teleseismic waves travelling through this crustal model are compared with those from the standard reference model IASP91 and the residuals are used to correct observed teleseismic arrival times at the SVEKALAPKO array. To test the performance of this approach, in a second part of the study a synthetic traveltime data set is obtained by tracing wave fronts through a mantle structure with known velocity anomalies and the 3-D crustal model. This data set is inverted with and without correction for crustal effects. The 3-D crustal effects alone with a homogeneous mantle are also inverted and the results show that the crustal effects propagate down to 450 km. The comparison of the inversion results demonstrates the need to apply appropriate 3-D crustal corrections in high-resolution regional tomography for upper-mantle structure beneath the Baltic Shield